2012
DOI: 10.1080/09720073.2012.11891264
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Desire and Expression among Girls in a Traditional Shona Context

Abstract: The study explored sexual fantasy, sexual desire, sexual expression, girl fertility awareness, and mubobobo among girls in a traditional Shona context. The study used snowballing technique to recruit participants. Inclusion in the study was voluntary. Teenage girls were asked about their sexuality in the era of HIV and AIDS. The study was qualitative in nature and used thematic content analysis to analyse the data. The girls described their experiences growing up following Shona traditions about puberty, sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Whether parents are comfortable having such conversations or are knowledgeable about the topic is another issue. Conversely, in many African cultures parents are not expected to be involved in their children's sexual health and wellbeing education 17 . While we acknowledge that intergenerational culture clashes and conflict can result from differing messages about sexual health and wellbeing our research found that it may not only be the messages, as often assumed, which ultimately result in a cultural clash.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether parents are comfortable having such conversations or are knowledgeable about the topic is another issue. Conversely, in many African cultures parents are not expected to be involved in their children's sexual health and wellbeing education 17 . While we acknowledge that intergenerational culture clashes and conflict can result from differing messages about sexual health and wellbeing our research found that it may not only be the messages, as often assumed, which ultimately result in a cultural clash.…”
Section: Discussionmentioning
confidence: 99%
“…The church may have also been most comfortable as it espouses an abstinencebased approach to sexual behaviour that mirrors the message the women endorsed with their children -a perspective supported by a range of African groups 7,8,11,12,16,17,25 . In order to gain parental endorsement of comprehensive sexual health and wellbeing programs future research could investigate individuals or institutions that migrant parents believe they can entrust with their children's sexual health and wellbeing education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the prominent challenges experienced by infertile women is stigma and adverse treatment by society. Women also suffer physical abuses and violence [13] while others are secluded from certain cultural practices even at death [15]. Although symptoms recognition in infertility may be difficult to identify as compared to other forms of sicknesses, it is assumed that women with infertility go through emotional and psychological challenges.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…At the individual level, childless women may face economic hardships, social segregation, violence, marital dissolutions, physical and emotional abuses [11][12][13][14]. Childless women may also be secluded from certain cultural practices and even at their death, special rituals may be performed to circumvent their infertility situation in the next world [15]. These practices depict that the entire society is against childlessness, hence their discontent and adverse attitudes towards people with infertility.…”
Section: Introductionmentioning
confidence: 99%